Endoscopic Suturing for the Prevention and Treatment of Complications Associated with Endoscopic Mucosal Resection of Large Duodenal Adenomas - Jaeil Chung; Kelly Wang; Alexander Podboy; Srinivas Gaddam; Simon K. Lo (Korean Society of Gastrointestinal Endoscopy, 2022)
Background/Aims Endoscopic mucosal resection (EMR) is the primary treatment for duodenal adenomas; however, it is associated with a high risk of perforation and bleeding, especially with larger lesions. The goal of this study was to demonstrate the feasibility and safety of endoscopic suturing (ES) for the closure of mucosal defects after duodenal EMR. Methods Consecutive adult patients who underwent ES of large mucosal defects after EMR of large (>2 cm) duodenal adenomas were retrospectively enrolled. The OverStitch ES system was employed for closing mucosal defects after EMR. Clinical outcomes and complications, including delayed bleeding and perforation, were documented. Results During the study period, ES of mucosal defects was performed in seven patients in eight sessions (six for prophylaxis and two for the treatment of perforation). All ES sessions were technically successful. No early or delayed post-EMR bleeding was recorded. In addition, no clinically obvious duodenal stricture or recurrence was encountered on endoscopic follow-up evaluation, and no patients required subsequent surgical intervention. Conclusions ES for the prevention and treatment of duodenal perforation after EMR is technically feasible, safe, and effective. ES should be considered an option for preventing or treating perforations associated with EMR of large duodenal adenomas.